Geranylgeraniol Restores Zoledronic Acid-Induced Efferocytosis Inhibition in Bisphosphonate-Related Osteonecrosis of the Jaw - Chen, Xin; Zhu, Weiwen; Xu, Rongyao; Shen, Xin; Fu, Yu; Cheng, Jie; Liu, Laikui; Jiang, Hongbing (Frontiers in Cell and Developmental Biology, 2021)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a severe side effect of long-term administration of bisphosphonates such as zoledronic acid (ZA), but its pathogenesis remains unclear. Impairment of the clearance of apoptotic cells (termed ‘efferocytosis’) by ZA may be associated with the pathogenesis of BRONJ. The aim of this study was to investigate whether ZA might inhibit macrophage efferocytosis and promote osteocytic apoptosis, and the underlying mechanisms responsible for the disturbing balance between clean and generation of osteocytic apoptosis. We found that ZA significantly promoted the apoptosis of osteocyte and pre-osteoblast via BRONJ mice models and in vitro MC3T3-E1, but also inhibited the efferocytosis of macrophage on apoptotic cells. Moreover, supplement with Geranylgeraniol (GGOH), a substrate analogue for geranylgeranylation of Rac1, could restore Rac1 homeostasis and rescue macrophage efferocytosis. GGOH partially inhibits MC3T3-E1 apoptosis induced by ZA via downregulation of Rac1/JNK pathway. We also examined the Rac1 distribution and activation conditions in bone marrow-derived macrophages (BMDMs) and MC3T3-E1 under ZA treatment, and found that ZA impaired Rac1 migration to BMDMs membrane, leading to round appearance with less pseudopodia and efferocytosis inhibition. Moreover, ZA simultaneously activated Rac1, causing overexpression of P-JNK and cleaved caspase3 in MC3T3-E1. Finally, the systemic administration of GGOH decreased the osteocytic apoptosis and improved the bone healing of the extraction sockets in BRONJ mice models. Taken together, our findings provided a new insight and experimental basis for the application of GGOH in the treatment of BRONJ.